Drying of a tape-cast layer: Numerical modelling of the evaporation process in a graded/layered material. (December 2016) - Jabbari, M.; Jambhekar, V.A.; Hattel, J.H.; Helmig, R.
Highlights: Coupled free-flow-porous-media simulation on REV scale. Drying behaviour of graded/layered materials. Numerical results motivated by ceramic tape casting. Abstract: Evaporation of water from a ceramic layer is a key phenomenon in the drying process for the manufacturing of water-based tape cast ceramics. In this paper we present a coupled free-flow-porous-media model on the Representative Elementary Volume (REV) scale for coupling non-isothermal multi-phase compositional porous-media flow — for the ceramic layer — and single-phase compositional laminar free flow — for the air above it. The preliminary results show the typical expected evaporation behaviour from a porous medium initially saturated with water, and water–vapour transport to the free-flow region in accordance with the available results from the literature. We elaborate on and discuss the characteristic drying-rate curve for a single layer ceramic, and compare it with that of a graded/layered ceramic. We, moreover, show the influence of the mean diameter of particles of the porous medium ( d p ) — which directly affects the intrinsic permeability ( K ) based on the well-known Ergun's equation — of each single ceramic layer on the drying behaviour of a graded/layered ceramic.